Template free synthesis of mesoporous TiO2 with high wall thickness and nanocrystalline framework - Kulkarni, Dhanashree G.; Murugan, A. Vadivel; Viswanath, Annamraju Kasi; Gopinath, Chinnakonda S. (Journal of Nanoscience and Nanotechnology, 2009)
A simple procedure to prepare nanocrystalline mesoporous titania (meso-TiO2) is reported without any templating agent and it possesses a high BET surface area and a large pore wall thickness (11.3 nm) than that of meso-TiO2 prepared by other methods. Nanocrystalline meso-TiO2 also has been synthesized with hexadecylamine template for comparison through known procedure. The meso-TiO2 materials were characterized by X-ray diffraction, FT-IR, UV-Vis absorbance spectra, thermal analysis, SEM, HRTEM and textural properties through N-2 adsorption-desorption isotherms. Spherical shape particles in a range of few hundred nanometers are obtained in the template free method. Above systematic characterization provides direct indications toward the mechanism of formation of meso-TiO2 in the template free method. A comparison of the physical and textural properties indicates a possibility of coarse-tuning of the textural characteristics of mesoporous TiO2 by adopting different preparation methods.
Keywords: Mesopore; Mesopore Formation; Template-Free; Thick Wall; titania

Toward an understanding of the molecular level properties of ziegler-natta catalyst support with and without the internal electron donor - Thushara, K. S.; Gnanakumar, Edwin S.; Mathew, Renny; Jha, Ratnesh Kumar; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Sarma, Krishna; Padmanabhan, Sudhakar; Bhaduri, Sumit; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2011)
Two Ziegler-Natta catalysts supported on molecular adducts, namely, MgCl2 center dot 6EtOH (ME) and MgCl2 center dot 5EtOH center dot EtOOCPh (Est-ME), have been prepared. A systematic effort has been made to unravel the molecular level structure property relationships of the catalysts and adducts. Ethylbenzoate is an internal electron donor, and its in situ formation through EtOH+PhCOCl coupling is successfully achieved. The above adduct has been treated with TiCl4, and the resultant catalyst (Ti/Est-ME) is evaluated for ethylene polymerization activity. Rand C-13 CP/MAS NMR of Est-ME (Ti/Est-ME) show carbonyl features at 1730 (1680) cm(-1) and 169 (170) delta, respectively, providing direct support for the presence of ester as an integral part. In spite of low surface area, Ti/Est-ME gives higher yield for ethylene polymerization than the one derived from ME. The results indicate that electronic environment is more important than surface area or any other single factor in determining the polymerization activity.

Toward a quantitative correlation between microstructure and DSSC efficiency: a case study of TiO2-xNx nanoparticles in a disordered mesoporous framework - Sivaranjani, Kumarsrinivasan; Agarkar, Shruti A.; Ogale, Satishchandra B.; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2012)
The efficiency (eta) of a dye-sensitized solar cell (DSSC) depends on various parameters, the critical factors being a fast charge carrier transport and a slow rate of electron-hole recombination. The present article describes a simple combustion synthesis method to prepare TiO2-xNx with following four important features that directly influences eta: (1) a disordered mesoporous structural framework with high surface area to give high dye-loading and a small diffusion length for charge carriers allowing rapid movement to the surface; (2) electrically interconnected nanocrystalline TiO2-xNx particles with good necking and predominant (101) anatase facets to minimize electron-hole recombination; (3) low charge storage capacity in the titania framework; and (4) surface unsaturation assisting all the above factors. The pseudo-three-dimensional nature of mesoporous TiO2-xNx with the above features demonstrates the importance of textural features, and porosity allows faster diffusion of charge carriers to surface and their utilization to generate power. A quantitative correlation between interconnected nanoparticles over larger distances in a mesoporous framework and eta is demonstrated. This study also demonstrates an inexpensive and rapid method of producing the photoanode material with high eta in about 10 min.

Towards a sustainable and near ambient DeNO(x) under lean burn conditions: a revisit to no reduction on virgin and modified pd(111) surfaces - Roy, Kanak; Jain, Ruchi; Gopinath, Chinnakonda S. (ACS Catalysis, 2014)
Catalytic conversion of NO in the presence of H-2 and O-2 has been studied on Pd(111) surfaces, by using a molecular beam instrument with mass spectrometry detection, as a function of temperature and reactants composition. N-2 and H2O are the major products observed, along with NH3 and N2O minor products under all conditions studied. Particular attention has been paid to the influence of O-2 addition toward NO dissociation. Although O-2-rich compositions were found to inhibit the deNO(x) activity of the Pd catalyst, some enhancement in NO reduction to N-2 was also observed up to a certain O-2 content. The reason for this behavior was determined to be the effective consumption of the H-2 in the mixture by the added O-2 and O atoms from NO dissociation. NO was proven to compete favorably against O-2 for the consumption of H-2, especially <= 550 K, to produce N-2 and H2O. Compared with other elementary reaction steps, a slow decay observed with the 2H + 0 -> H2O step under SS beam oscillation conditions demonstrates its contribution to the rate-limiting nature of the overall reaction. Pd(111) surfaces modified with O atoms in the subsurface (Md-Pd(111)) induces steady-state NO reduction at near-ambient temperatures (325 K) and opens up a possibility to achieve room temperature emission control. A 50% increase in the reaction rates was observed at the reaction maximum on Md-Pd(111), as compared with virgin surfaces. Oxygen adsorption is severely limited below 400 K, and effective NO + H-2 reaction occurs on Md-Pd(111) surfaces. Valence band photoemission with a UV light source (He I) under different oxygen pressures with APPES clearly identified the characteristics of the Md-Pd(111) surfaces and PdO. The electron-deficient or cationic nature of Md-Pd(111) surfaces enhances the NO dissociation and inhibits oxygen chemisorption <= 400 K under lean-burn conditions.
Keywords: deNO(x); heterogeneous catalysis; Hydrogen; lean burn; molecular beam; nitric oxide; Palladium; surface modification

Is there any real effect of low dimensional morphologies towards light harvesting? a case study of Au-rGO-TiO2 nanocomposites - Melvin, Ambrose A.; Bharad, Pradnya A.; Illath, Kavya; Lawrence, Meenu P.; Gopinath, Chinnakonda S. (Chemistry Select, 2016)
Nanotube and nanosheet morphologies have been celebrated for their electron transport properties. Present work has been explored to exploit the same by combining 1D TiO2 nanotube (1D-TN) with 2D reduced graphene oxide (rGO) along with nano gold for visible light sensitization for photocatalytic H2 generation under one sun condition and visible light (λ≥ 400 nm). Vertical and horizontal electron transport in 1D-TN and rGO, respectively, is combined with the visible light absorption capability of Au nanoparticle. H2 yield (HY) varies between 100 and 655 µmol/g.h with an apparent quantum yield between 0.45 and 3.2 %, respectively, depending on Au/rGO/1D-TN preparation method and reaction conditions. It has been demonstrated that interfacial contact between rGO/1D-TN and Au is crucial for high photocatalytic HY. Preparation method influences charge utilization, and hence HY, to a large extent. Nonetheless, the maximum HY reported in the present work is just comparable to HY reported in literature with the most commonly found spherical morphology, and this leads to a question of, is there any real influence of 1D and/or 2D materials, particularly, towards light harvesting applications?

Three way catalytic converter reactions aspects at near ambient temperatures on modified pd-surfaces - Roy, Kanak; Jain, Ruchi; Ghosalya, Manoj Kumar; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (Comptes Rendus Chimie, 2016)
The dissolution of oxygen in palladium plays an important role in palladium catalysis. The present study shows that the surface modification (SM) due to the dissolution of atomic oxygen into the subsurfaces of palladium can be used as a control to tune its catalytic activity. CO oxidation and NO + H-2 + O-2 reaction was separately carried out on metallic Pd and on surface modified Pd using a molecular beam instrument and the results were compared. The metallic Pd does not show activity below 400 K for both reactions, whereas the SM-Pd shows activity at near-ambient temperatures. The electronic change due to SM was investigated using ambient pressure photoelectron spectroscopy, and the investigation clearly shows the effect of subsurface oxygen in the ambient temperature activity of palladium. (C) 2016 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.

Thin-film approach for scalability and enhancement of solar hydrogen production with CNT integrated Ce-doped-TiO2 composite in direct sunlight - Vijayarengan, Preethi; Maria, Anthony Raja; Ashadevi, K. S.; Nalajala, Naresh; Gopinath, Chinnakonda S. (Materials Today Catalysis, 2025)
<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Solar hydrogen production by photocatalysis has long been considered as an important energy option. Whichever photocatalyst succeeds, methods should be available to scale-up in a most sustainable and cost-effective manner, and the present work addresses this specific issue. In the present study, Ce-doped in the TiO<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> lattice (Ce-TiO<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">) and the same integrated with CNT (CNT-Ce-TiO<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">; (CCT)) composite was synthesized and characterized. Current study demonstrates the synergistic integration of Ce-TiO₂ as a light absorber and charge generator with CNTs as efficient charge separation at heterojunctions as well as charge transporter in a thin-film configuration (lab-scale (4.7 cm<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">), bench-scale (500 cm<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">)). Improved H<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> generation under direct sunlight demonstrated in thin film form, than in particulate suspension, is attributed to efficient light absorption, particularly for electron-hole pair separation and their dispersion to redox sites. Additionally, the role of the binder is highlighted for improving H<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> yield and the sustainability of the thin-film form of photocatalyst. ∼200 mg (1 g) CCT coated over 500 cm<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> (2500 cm<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">) photocatalyst produced 21.6 mmol/h (102 mmol/h) H<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> in sunlight. Present results provides a proof of concept that the thin film form of photocatalyst displays, at least 10 times, higher H<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> yield than its powder counterpart, depending on the measurement conditions. A non-linear enhancement in H<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> yield with small and large area thin-film indicates complex underlying factors and highlights the scope for further improvements.